PENGARUH JALAN PAGI TERHADAP PERUBAHAN TEKANAN DARAH PADA LANJUT USIA DENGAN HIPERTENSI DI DESA KALIANGET TIMUR KECAMATAN KALIANGET KABUPATEN SUMENEP (The Effect of Walking in the Morning to Change of Blood Pressure in Elderly with Hypertension in Kaliang - Puspitasari, Dian Ika; Hannan, Mujib; Chindy, Leviana Dea (Fakultas Keperawatan, Universitas Katolik Widya Mandala Surabaya, 2017)
Introduction: Walking in the morning is a mild activity suitable for elderly people as it can help control blood pressure in the long term. Inability of the elderly to perform daily physical activity can affect blood pressure changes. This study aims to analyze the influence of walking in the morning to changes in blood pressure in the elderly with hypertension. Method: This research pre-experiment design is using one group pre-post test design, with simple random sampling technique. The population in this study were elderly with hypertension in Kalianget Timur Village as many as 71 people, 60 samples. Data analysis using Wilcoxon statistical test. Results: The results showed that before walking in the morning is most (65%) blood pressure sistole 140-159 mmHg and diastole blood pressure entirely (100%)> 100 mmHg. Then after walking in the morning blood pressure decreases most (55%) sistole blood pressure is 140-159 mmHg and almost all (88.3%) diastole blood pressure> 100 mmHg. The result of data analysis obtained p = 0,000 (